Kesadaran Wajib Pajak, Penghapusan Sanksi, Pembebasan Bea Balik Nama, e-SAMSAT dan Kepatuhan Wajib Pajak - Wijayanti, Ni Made Windi; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi, 2024)
The aim of this research is to obtain empirical evidence about the influence of taxpayer awareness, elimination of PKB sanctions, BBNKB exemption, and e-SAMSAT on motor vehicle taxpayer compliance in Badung Regency. The research location is at the SAMSAT Joint Office, Badung Regency. The accidental sampling method is a method for determining the sample and the number of samples is calculated using the Slovin formula to obtain 100 samples. Data collection was carried out through a survey method using a questionnaire and the analysis technique used was multiple linear regression analysis with the SPSS analysis tool. This research shows that taxpayer awareness, elimination of PKB sanctions, BBNKB exemption and e-SAMSAT have a positive effect on motor vehicle taxpayer compliance in Badung Regency. Keywords: Awareness; Tax Reduction; BBNKB Exemption; eSAMSAT; Taxpayer Compliance.